Rapid microwave synthesis and optical activity of highly crystalline platinum nanocubes. (14th January 2018) - Davis-Wheeler Chin, Clare; Akbarian-Tefaghi, Sara; Reconco-Ramirez, Juana; Wiley, John B.
Abstract: Abstract : We have developed a novel, facile, and reproducible synthesis of highly crystalline oleylamine-capped colloidal platinum nanocubes by microwave (MW) heating. Use of MW heating decreases reaction times, eliminates the need for dangerous reagents [e.g., Fe(CO)5 ], and gives efficient production of monodispersed 8 nm Pt nanocubes [MW-nanoparticles (NPs)]. We also present a study of the optical properties of these NPs, which to our knowledge has not been previously reported. Absorbance spectra of the MW-NPs show a distinct localized surface plasmon resonance band at 213 nm. This observation could be significant for developments in plasmonic photocatalysis and advanced catalytic materials.